Implementation of Sound Effects and Voice Over Techniques in Creating Motion Graphic “Budidaya Ayam Kampung Unggul Balitbangtan” - Ihsanul Hadi; Amata Fami; Benito Ibrahim Delano (Jurnal Pendidikan Multimedia (Edsence), 2023)
In the current era of technological advances used to provide information has grown very rapidly. Various kinds of media are used, one of them is Motion Graphic. The motion graphic entitled "Budidaya Ayam Kampung Unggul Balitbangtan" aims to make people aware of how to cultivate Ayam Kampung Unggul Balitbangtan. Motion graphics have several important things, one of which is voice-over and sound effects, because they can convey messages well to the community. In the process of making it can start with designing, then proceed with production and end with product testing. The making of this motion graphic refers to the method from the e-book Motion Graphics Budidaya Ayam Kampung Unggul Balitbangtan. Voice-over and sound effects used greatly affect the final result of the motion graphic made Both of them can present the topics that are displayed to the public and the public can understand the intent and purpose of this motion graphic. Voice-over cannot only be applied to motion graphics but can also be applied to commercial videos.